ANALISIS EPIC MODEL TERHADAP EFEKTIVITAS VIDEO PROMOSI MELALUI MEDIA SOSIAL - Puput Arisna; Ilham Juliwardi; Meutia Qudraty (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Globalization, which is supported by advances in technology and information, is one of the leading accesses for the public in accessing sources of information and utilizing them for life and the economy. Internet access and its features are an opportunity for the community to improve their welfare more easily, creatively and efficiently. One feature that is widely used by the public is social media. Social media is also used as a means of promotion to increase branding more effectively. This study aims to measure the level of promotion effectiveness through social media by using the EPIC Model as an analytical method for the promotional videos for Development Economics at Teuku Umar University and the sampling technique using Random Sampling by distributing questionnaires. This study shows the results that promotion through social media is included in the very effective scale range with an EPIC Rate of 3,51. Specifically, the calculation results for the empathy dimension are 3,51, the persuasion dimension is 3,56, the impact dimension is 3,51 and the communication dimension is 3,54